Differential Impact of Magnitude, Polyfunctional Capacity, and Specificity of HIV-Specific CD8(+) T Cell Responses on HIV Set Point - Riou, Catherine (American Society for Microbiology, 2014)
Defining the characteristics of HIV-specific CD8(+) T cell responses that lead to viral control is crucial for vaccine development. We evaluated the differential impact of magnitude, polyfunctional capacity, and specificity of the CD8(+) response at approximately 6 months postinfection on the viral set point at 12 months in a cohort of HIV-infected individuals. High frequencies of Gag and Nef responses endowed with four functions were the best predictors of a low viral set point.